From Chicago to Hollywood: the Metamorphosis of V.I. Warshawski - Nicole Décuré (Sillages Critiques)
The passage from novel to film is often a difficult one. When it comes to feminist fiction, the problem becomes acute because the ideology of Hollywood combined with that of a male director find it hard to accommodate such a vision. Taking as an example Sara Paretsky’s crime fiction series, with its private detective heroine V.I. Warshawski, and Jeff Kanew’s adaptation for the Disney studios, the article attempts to show how the subversive elements of the novels are weakened in the film and the unconventional heroine finds herself in the eternal roles of seductress and mother, which she is not in the fiction. The body becomes object (for the male gazer), the woman is minimized in her enterprises through ridicule or cheap, sometimes gross, comedy. Fortunately, the film turned out to be a commercial failure.